2015
DOI: 10.1021/ct501072t
|View full text |Cite
|
Sign up to set email alerts
|

A Collective Variable for the Rapid Exploration of Protein Druggability

Abstract: An efficient molecular simulation methodology has been developed for the evaluation of the druggability (ligandability) of a protein. Previously proposed techniques were designed to assess the druggability of crystallographic structures and cannot be tightly coupled to molecular dynamics (MD) simulations. By contrast, the present approach, JEDI (Just Exploring Druggability at protein Interfaces), features a druggability potential made of a combination of empirical descriptors that can be collected "on-the-fly"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 73 publications
0
36
0
Order By: Relevance
“…Thus hPNMT has been used to test other algorithms for cryptic pockets such as JEDI. 34 From 1HNN to 2G8N, the pocket volume increases when the protein is in complex with a selective inhibitor (3-Hydroxymethyl-1,2,3,4-tetrahydroisoquinoline or F83), which requires the displacement of the K57 side chain, and a small movement of the α3 helix (see Fig. 1 d left).…”
Section: Hpnmtmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus hPNMT has been used to test other algorithms for cryptic pockets such as JEDI. 34 From 1HNN to 2G8N, the pocket volume increases when the protein is in complex with a selective inhibitor (3-Hydroxymethyl-1,2,3,4-tetrahydroisoquinoline or F83), which requires the displacement of the K57 side chain, and a small movement of the α3 helix (see Fig. 1 d left).…”
Section: Hpnmtmentioning
confidence: 99%
“…their hydrophobicity) such as JEDI are being actively developed, but they still require prior knowledge of the cavity location. 34 At the other end of the spectrum are machine learning approaches such as Cryptosite, a hidden sites identification tool. They show promise, but are limited by the scarce availability of experimentally-determined cryptic pockets and lack the atomic-level insight that MD-based approaches can provide.…”
Section: Introductionmentioning
confidence: 99%
“…10,34,71,72 These methods analyze the cavities over static structures coming from experiments or simulations such as DrugPred, 73 Cavity 74 or fpocket, 75 or coupled to MD simulations and calculate the druggability "on-the -fly", such as the recently developed JEDI. 76 Zhang and coworkers 44 have studied the ligand-binding cavities of diverse IDPs comparing some of their properties with those of ordered proteins. They concluded that IDPs are predicted to possess more binding cavities than ordered proteins of a similar length, showing different geometries.…”
Section: Binding Cavity Detection and Understandingmentioning
confidence: 99%
“…To that extent, usual CAAD techniques can be useful to estimate the druggability and the effects of small molecules on IDP interactions [10,34,71,72]. These methods analyze the cavities over static structures coming from experiments or simulations such as DrugPred [73], Cavity [74] or fpocket [75], or coupled to MD simulations and calculate the druggability "on-the -fly", such as the recently developed JEDI [76].…”
Section: Binding Cavity Detection and Understandingmentioning
confidence: 99%